Improving Students’ Vocabulary Mastery Through Quizizz Application as Game Based Learning - Aseptiana Parmawati; Siti Ruqoyyah (Jurnal Pendidikan Edutama, 2023)
Abstract: Mastering vocabulary is very important for foreign language learners. Since today’s era demands teacher and lecturer to deal with technology in teaching, the role of technology is really important.  E-learning as the concept of computer and network-based learning can be used by the educators in this era. One of the e-learning media is quizizz. The purpose of this research: to find out the improvement of student’s vocabulary through Quizziz application as game based learning. The subject of this research consist of 20 students in one of senior high schools in Cimahi. The design of this research is Classroom Action Research (CAR). Test and Questionnaire as instruments in this research. From the result of pre-test, the researchers found that the result of students’ vocabulary mastery was under average and still far from what was expected. The finding was supported by the result of students’ vocabulary scores. The average score of pre-test was 64,67. After the implementation of Quizizz in every cycle, the students’ vocabulary score were getting better. It can be seen from the result of students’ average score Cycle 1 was 71,37 and Cycle 2 was 81,31. It can be concluded that Quizizz can improve students’ vocabulary mastery and Quizizz can improve vocabulary classroom into a better situation.Abstrak: Menguasai kosakata sangatlah berguna bagi mempelajari Bahasa. Di era sekarang ini, guru dan dosen harus dapat menguasai teknologi dalam pembelajaran, maka keberadaan para guru tersebut memiliki peran penting. E-learning merupakan lonsep dari computer dan network based learning, yang dapat berguna bagi pelajar saat ini. Salah satu media pembelajaran e learning yang dapat digunakan adalah Quizizz. Tujuan dari penelitian ini adalah untuk mengetahui sejauh mana peningkatan kemampuan kosakata siswa melalui aplikasi Quizizz sebagai media pembelajaran berbasis game. Subjek dari penelitian ini berjumlah 20 siswa dari sebuah sekolah tinggi di wilayah Cimahi. Desain dari penelitian ini adalah Penelitan Tindakan Kelas. Test dan Quesioner digunakan sebagai instrument dalam penelitian ini. Dari hasil pre test, peneliti dapat menyimpulkan bahwa kemampuan penguasaan kosakata siswa masih jauh dari yang diharapkan. Hal tersebut mengacu pada nilai score yaitu 64,67. Setelah mengimplementasikan Quizizz di setiap siklunya, nilai siswa mengalami peningkatan. Hal tersebut dapat dilihat dari hasil tes di siklus 1 yaitu 71,37 dan 81,31 untuk siklus 2. Dari hasil penilaian tersebut maka dapat disimpulkan bahwa Quizizz dapat meningkatkan kemampuan penguasaan kosakata siswa, selain itu situasi kelas juga menjadi lebih baik.